Factor IX Denver, ASN 346→ASP Mutation Resulting in a Dysfunctional Protein with Defective Factor VIIIa Interaction - Lefkowitz, Jerry B.; Nuss, Rachelle; Haver, Tara; Jacobson, Linda; Thompson, Arthur R.; Manco-Johnson, Marilyn (Thrombosis and Haemostasis, 2001)
Hemophilia B is a sex-linked recessive bleeding disorder characterized by the presence of either a decreased amount of normal factor IX (FIX) or the presence of a dysfunctional FIX. We have identified a unique mutation in a family with mild hemophilia B. DNA analysis of family members revealed a single base transition in the 8th exon of the FIX gene predicting an amino acid change of Asn 346→Asp in the catalytic domain. The FIX variant, named FIX Denver, was purified from proband plasma. Kinetic studies of factor X (FX) interactions with normal FIXa or FIXa Denver and phospholipid (PL) showed little difference in kcat, but a significant difference when factor VIIIa (FVIIIa) was included in the reaction. Using kinetic assays to infer the Kd of FIXa for FVIIIa, normal FIXa had a Kd of 0.095 nM while that of FIXa Denver was 9.85 nM. The major defect caused by this point mutation is a marked decrease in the affinity of FIXa Denver for factor VIIIa.
Keywords: Factor IX; factor VIII; factor X; hemophilia B; hemorrhage